The crustal accretion history and tectonic evolution of the NE China segment of the Central Asian Orogenic Belt - Zhou, J.; Wilde, Simon (Elsevier Science BV, 2013)
The basement rocks in parts of NE China constitute a khondalitic sequence of sillimanite- and garnet-bearing gneisses, hornblende–plagioclase gneiss and various felsic paragneisses. Zircon U–Pb dating of garnet–sillimanite gneiss samples from the Erguna, Xing'an, Jiamusi and Khanka blocks indicates that highgrade metamorphism occurred at ~500 Ma. Evidence from detrital zircons in Paleozoic sediments from the Songliao Block also indicates the former presence of a ~500 Ma component. This uniformity of U–Pb ages across all crustal blocks in NE China establishes a >1300 km long Late Pan-African khondalite belt which we have named the ‘NE China Khondalite Belt’. This indicates the blocks of NE China were amalgamated prior to ~500 Ma, contrary to current belief. One scenario is that this amalgamated terrane had a tectonic affinity to the Siberia Craton, once forming part of the Late Pan-African (~500 Ma) Sayang–Baikal orogenic belt extensively developed around the southern margin of the Siberia Craton. This belt was the result of collision between currently unidentified terranes with the Southeastern Angara–Anabar Province at about 500 Ma, where the rocks were deformed and metamorphosed to granulite facies. It appears likely that at sometime after ~450 Ma, the combined NE China blocks rifted away from Siberia and moved southward to form what is now NE China.The combined block collided with the North China Craton along the Solonker–Xar Moron–Changchun suture zone at ~ 230 Ma rather than in the end-Permian as previously thought. Local rifting at the eastern extremity of the developing Central Asian Orogenic Belt (CAOB) resulted in the splitting away of the Jiamusi/Khanka(/Bureya) blocks. However, this was only transient and sometime between 210 and 180 Ma, these were re-united with the CAOB by the onset of Pacific plate subduction, which has dominated the tectonic evolution of the region since that time.